"GLOBALISING SOVEREIGNTY"? PETTIT'S NEO-REPUBLICANISM, INTERNATIONAL LAW, AND INTERNATIONAL INSTITUTIONS. (28th August 2015) - Thomas, Christopher Alexander
Abstract: This article explores Philip Pettit's recent attempts to extend his republican theory of justice and legitimacy to the international sphere in accordance with his ideal of "globalised sovereignty", with a specific focus on his treatment of international law and institutions. It uses the practice of international law and institutions, with examples largely drawn from international economic law, to test the assumptions built into Pettit's theory. It then considers whether and how some of those assumptions might need to be revised in light of the legal, institutional, and practical constraints of the international domain.